Acute Effect of Cigarette Smoking on HRV in Current Cigarette Smokers - Ferdous, Mehboba; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2015)
Background:Cigarette smoking induced increased sympathetic activity is one of the major independent risk factor for cardiac morbidity and mortality. Objective:To assess acute effects of smoking on neuro cardiovascular regulation by analysis of time domain measures of HRV in current regular healthy male cigarette smoker. Methods:This comparative analytical study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from July 2011 to June 2012. 120 apparently healthy male current regular cigarette smoker aged 20-55 years were participated in the study group. Age and BMI matched 70 apparently healthy male non smoker subjects were studied as control. To observe the acute effects data were recorded 5 and 30 min after finishing a cigarette. Time domain measures of HRV were recorded by a RMS digital polyrite D. Statistical analysis was done by independent sample t test and paired sample t test. Results: Resting pulse rate, SBP, DBP, mean heart rate were significantly higher (p<0.001) and mean R-R interval, SDNN, RMSSD and total power were significantly lower (p<0.001) in all smokers in comparison to those of healthy control.In addition, all time domain parameters were significantly decreased from their corresponding baseline value just 5 minutes after smoking and returned close to their baseline value after 30 minutes of smoking but it remained significantly lower than control value. Conclusion: The result of this study concludes that cigarette smoking had acute effect on cardiac autonomic function causing depressed vagal activity and overbalance of sympathetic function. DOI: http://dx.doi.org/10.3329/jbsp.v9i2.22798 Bangladesh Soc Physiol. 2014, December; 9(2): 59-64